CLINICAL PRESENTATION OF HIV-INFECTED PATIENTS IN A PSYCHIATRIC HOSPITAL IN SOUTH AFRICA - Chetty, Shren; Naidu, Kalai (African Journal of Infectious Diseases (AJID), 2018)
Background: Africa is profoundly stricken by the HIV pandemic. People living with HIV/AIDS are more likely to be diagnosed with psychiatric disorders than the general population. We describe the prevalence of different mood and psychiatric disorders in HIV/AIDS infected patients with serious mental illness. Materials and Methods: We retrospectively sourced data from 105 patient files, at Weskoppies Hospital, between January 2012 and December 2016. Results: 56 patients had a psychotic disorder; 27 patients had a mood disorder and three patients had a cognitive disorder. Multiple diagnoses were observed in seven patients with a mood and psychotic disorder; ten patients with a psychotic and cognitive disorder and one patient with a mood and cognitive disorder. One patient had all three diagnoses. The most common medical co-morbidities were hypertension (15.24%) and tuberculosis (13.33%). Conclusion: Mentally ill patients who are HIV positive mostly present with mood and psychotic disorders. Clinicians need to be vigilant to detect neuropsychiatric manifestations of HIV infection to effectively manage and optimise treatment. This study highlights the need for further intervention in these vulnerable patients.